The Tyche of Berytus: a Phoenician goddess on civic coinage. - Kropp, Andreas (Mohr Siebeck, 2015)
This contribution deals with images of Tyche on the civic bronze coinage of the Roman colony of Berytus (Beirut). The visual type of this local patron goddess, a hybrid composition drawing on a variety of iconographic sources, was created in the late first or early second century CE and quickly adopted by cities across the Near East. The meanings of such local divine images are rarely explored. When examined in their proper context, the seemingly generic images of Tyche can be shown to be meaningful to the community in many different ways. With a wider appeal than any other coin types, the Tyche of Berytus stood as the universally acknowledged badge of the city and expressed the collective values of the community. The study of the genesis and meaning of this ‘new’ type of goddess throws a light on the cultural and religious life of Roman Phoenicia.